2022
DOI: 10.18632/aging.203960
|View full text |Cite
|
Sign up to set email alerts
|

Hallmarks of aging-based dual-purpose disease and age-associated targets predicted using PandaOmics AI-powered discovery engine

Abstract: Aging biology is a promising and burgeoning research area that can yield dual-purpose pathways and protein targets that may impact multiple diseases, while retarding or possibly even reversing age-associated processes. One widely used approach to classify a multiplicity of mechanisms driving the aging process is the hallmarks of aging. In addition to the classic nine hallmarks of aging, processes such as extracellular matrix stiffness, chronic inflammation and activation of retrotransposons are also often cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 104 publications
(101 reference statements)
1
54
0
Order By: Relevance
“…During the target identification process, our AI models dynamically assessed disease targets based on a variety of measures, such as novelty, accessibility by small molecules and biologics, safety and tissue expression specificity, to collectively generate hypotheses around their potential druggability profiles. Previous studies demonstrated the effectiveness of PandaOmics to identify novel and repurposing therapeutic targets ( Insilico Medicine, 2022 ; Pun et al, 2022 ; Vera et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…During the target identification process, our AI models dynamically assessed disease targets based on a variety of measures, such as novelty, accessibility by small molecules and biologics, safety and tissue expression specificity, to collectively generate hypotheses around their potential druggability profiles. Previous studies demonstrated the effectiveness of PandaOmics to identify novel and repurposing therapeutic targets ( Insilico Medicine, 2022 ; Pun et al, 2022 ; Vera et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…To address these challenges, increased utilization of database searches, biological assays, and machine learning techniques have been implemented to better identify targets of interest (12)(13)(14)(15). These techniques have been used to advance research in the field of neurodegeneration, with a specific focus on AD.…”
Section: Introductionmentioning
confidence: 99%
“…The careful consideration of targets identified with machine learning techniques in the context of biological processes is necessary to assess the feasibility and actionability of the identified targets. One such approach is taken by Pun et al ., (2022) by using the PandaOmics platform to investigate targets associated with aging and age-associated diseases from human cross-sectional data based on the nine hallmarks of aging (12). Although the use of human data to identify targets is highly relevant for drug discovery, obtaining rich longitudinal data to understand disease progression across an individual’s lifespan has remained extremely challenging.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations